TECHNIKI OBRAZOWANIAA case of acute pulmonary embolism in the course of primary pulmonary trunk tumour treated by surgery - Głowacki, Jan; Filipiak, Krzysztof; Lekston, Andrzej; Kaliś, Robert; Gałecka, Maria; Nożyński, Jerzy; Miszalski-Jamka, Karol; Greiff, Małgorzata; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
The authors present a case of a 59-year-old man admitted to the hospital with the diagnosis of acute pulmonary embolism. After an additional diagnostic process including multislice computed tomography of pulmonary arteries, chest and abdomen the patient was sent to surgery where, besides the emboli, a tumour of the pulmonary trunk and pulmonary arteries was removed. On the basis of immunohistochemistry the diagnosis of leiomyosarcoma, high grade, was established. The authors analyzed the pre-surgery symptoms of this rare tumour and concluded that the pulmonary embolism can obscure them. Only surgery can prolong the patient’s life so the diagnostic process must take the possibility of tumour into consideration.